Avaliação da produção de xilo-oligossacarídeos a partir de casca de soja - Fonseca, Murilo Amaral (2015)
Xylooligosaccharides (XOS) are short-chain polymers of xylose (2 to 7 units) which can be produced by enzymatic hydrolysis of the xylan from the lignocellulosic feedstocks. XOS have a great potential as probiotic ingredients, and when they are incorporated in diets, they can provide many health benefits. The worldwide interest in the use of lignocellulosic residues is constantly growing, and in this scenario the soybean hull arises as a potential residue of the Brazilian agroindustry. The bioconversion of these residues to value-added products requires suitable pretreatments to deconstruct/disorganize the recalcitrant lignocellulosic complex, separating its main fractions: cellulose, hemicellulose, and lignin. In this context, this work did evaluate different biomass pretreatments aiming to produce XOS by the action of a Bacillus subtilis endoxylanase. Initially, the conditions for maximum catalytic activity of this enzyme were evaluated changing pH, buffer, and temperature. Among these parameters, 50 mM citrate buffer, pH 5.5, and 45 oC were the one that gave highest activity. The in nature soybean hull (previously chemically characterized) was hydrolyzed with soluble endoxylanase with different enzyme loads (40, 80, and 100 U/g biomass) under preestablished pH and temperature, producing around 55 mg RS/g dry biomass. This result, though little expressive, showed the viability of XOS production from soybean hull. However, this approach requires a suitable pretreatment of the lignocellulosic biomass to improve the endoxylanase accessibility to the C-5 fraction. Several pretreatments were performed in the soybean hulls, such as, enzymatic deproteinization, hydrogen peroxide/acetic acid pretreatment, and organosolv-ethanol pretreatment. For some pretreatments, reagent concentration and reaction time were evaluated, as well as, sequential pretreatment. Besides, enzymatic hydrolysis of the in nature soybean hull under microwave irradiation was also evaluated. The deproteinization of the soybean hull was not very efficient to the enzymatic hydrolysis of the remnant solid (production of 30 mg RS/dry biomass). However, this pretreatment allows the protein recovery as a high nutritional value hydrolysate. The pretreatment of the deproteinized soybean hulls with hydrogen peroxide solution (5 M, 1 h) removed 56% lignin without cellulose losses. However, this pretreatment did not contribute to an efficient action of the endoxylanase to the hemicellulose fraction (production of around 30 mg RS/g dry biomass). The organosolv-(50% v/v)ethanol pretreatment of the deproteinized soybean hulls promoted the removal of around 50% lignin, with low solubilization of hemicellulose (<17%), producing a poor substrate for the endoxylanase. The organosolv pretreatments with 50 and 70% (v/v) ethanol of the in nature soybean hull were able to solubilize around 30% hemicellulose, allowing the production of around 76 and 49 mg RS/g dry biomass, respectively, after hydrolysis with endoxylanase. Finally, the microwave action on the lignocellulosic biomass probably decreased the biomass recalcitrance, because the hydrolysis of the in nature soybean hulls catalyzed by the endoxylanase (100 IU / g of biomass) yielded approximately 100 mg of RS/g dry biomass. On the other hand, the hydrolysis performed in a reactor under conventional heating produced only 52 mg RS/g dry biomass. The results of this work did show that the combination of microwave irradiation and enzymatic hydrolysis might be a promising alternative to produce XOS. Keywords: soybean hulls; xylo-oligosaccharides; pretreatments